Why is impact measurement abandoned in practice? Evidence use in evaluation and contracting for five European Social Impact Bonds. (January 2023) - Hevenstone, Debra; Fraser, Alec; Hobi, Lukas; Geuke, Gemma
Despite broad consensus on the importance of measuring "impact, " the term is not always understood as estimating counterfactual and causal estimates. We examine a type of public sector financing, "Social Impact Bonds, " a scheme where investors front money for public services, with repayment conditional on impact. We examine five cases in four European countries of Social Impact Bonds financing active labor market programs, testing the claim that Social Impact Bonds would move counterfactual causal impact evaluation to the heart of policy. We examine first how evidence was integrated in contracts, second the overall evidence generated and third, given that neither contracts nor evaluations used counterfactual definitions of impact, we explore stakeholders' perspectives to better understand the reasons why. We find that although most stakeholders wanted the Social Impact Bonds to generate impact estimates, beliefs about public service reform, incentives, and the logic of experimentation led to the acceptance of non-causal definitions.